“I TOOK A DEEP BREATH AND CAME OUT AS GC”: EXCAVATING GENDER CRITICAL INFORMATION LITERACY PRACTICES AND ANTI-TRANS RADICALIZATION ON OVARIT AND MUMSNET - Berge, PS; Schmalzer, Madison (AoIR Selected Papers of Internet Research, 2025)
In 2020, the subreddit r/GenderCritical—one of the most active “gender critical” (GC) spaces on Reddit—was banned by the platform for promoting hateful, transphobic conduct. Following the closure of r/GenderCritical (and subsequent banning of dozens of high-profile, transphobic subreddits including r/ActualWomen, r/GenderCriticalSociety, and r/truelesbians), GC users—especially those in North America and Western Europe—migrated to more hidden, invite-only spaces. These included Discord servers as well as (much like alt-right alternative platforms Parler and Truth Social) platforms run by GCs themselves: Spinster.xyz, the short-lived Giggle app, subforums on Mumsnet, and Ovarit—an invite-only forum which imitates Reddit’s architecture launched by former moderators of r/GenderCritical. While we might celebrate the closure of openly hateful communities on major social platforms, a crucial side-effect of the GC dispersal is that their activity has become (following patterns in reactionary political movements online more broadly) increasingly shrouded and insular. In this project, we provide an overview of the current landscape of GC activity on social media as it exists in the post-r/GenderCritical era. We describe how users are “peaked” (the GC equivalent of “redpilled”) and pipelined from algorithmic media platforms into insular and extremist spaces such as Ovarit, Mumsnet, and Discord. We then examine discourse within two popular GC forums, Ovarit and Mumsnet (specifically: Mumsnet’s “Feminism: Sex & gender” board), to identify how these groups circulate disinformation, perform political mythmaking, and construct and reinscribe reactionary identities in the context of GC ideology and extremism.